News writing - McKane, Anna (SAGE, 2014)
The ability to hone and craft an eye catching news story is fundamental to good journalism. It is an essential skill that all journalists must carry with them. The growth of online journalism and of social media has meant that the skills required in news writing are evolving, opening up fresh challenges and exciting new possibilities.